Overexpression of hsa-miR-125b during osteoblastic differentiation does not influence levels of Runx2, osteopontin, and ALPL gene expression - Pinto,M.T. (2013)
Multipotent mesenchymal stromal cells (MSCs) were first isolated from bone marrow and then from various adult tissues including placenta, cord blood, deciduous teeth, and amniotic fluid. MSCs are defined or characterized by their ability to adhere to plastic, to express specific surface antigens, and to differentiate into osteogenic, chondrogenic, adipogenic, and myogenic lineages. Although the molecular mechanisms that control MSC proliferation and differentiation are not well understood, the involvement of microRNAs has been reported. In the present study, we investigated the role of miR-125b during osteoblastic differentiation in humans. We found that miR-125b increased during osteoblastic differentiation, as well as Runx2 and ALPL genes. To study whether the gain or loss of miR-125b function influenced osteoblastic differentiation, we transfected MSCs with pre-miR-125b or anti-miR-125b and cultured the transfected cells in an osteoblastic differentiation medium. After transfection, no change was observed in osteoblastic differentiation, and Runx2, OPN, and ALPL gene expression were not changed. These results suggest that the gain or loss of miR-125b function does not influence levels of Runx2, OPN, and ALPL during osteoblastic differentiation.